2020
DOI: 10.1186/s12889-020-8217-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of modifiable cardiovascular risk factors in Yazd inner-city municipalities

Abstract: Background: Cardiovascular disease (CVD) is the leading cause of death in the world. With effective intervention and control of cardiovascular risk factors, mortality rates may be reduced. The aim of this study was to investigate the prevalence of modifiable risk factors across five municipalities in Yazd city.Methods: Ten thousand residents of the Yazd greater area aged 20-69 years were selected using cluster random sampling method. Overall, 200 clusters were randomly selected based on the postcodes of reside… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Mirzaei et al . conducted a study in Yazd, Iran and reported that lack of physical activities and unhealthy eating habits were among the most prominent risk factors of CVDs in a healthy society [ 37 ]. They also reported that 26.5% of Iran’s healthy population would be prone to the high risk of CVDs based on the Framingham risk score (FRS) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mirzaei et al . conducted a study in Yazd, Iran and reported that lack of physical activities and unhealthy eating habits were among the most prominent risk factors of CVDs in a healthy society [ 37 ]. They also reported that 26.5% of Iran’s healthy population would be prone to the high risk of CVDs based on the Framingham risk score (FRS) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the participants in this sample had low levels of physical exercise, supplemented by moderate and high levels. This study’s low prevalence of physical activity is higher than those seen in Somaliland (78.4%) [ 29 ], Kathmandu (61.1%) [ 11 ], Bolivia (64.77%) [ 33 ], and Iran (52.2%) [ 34 ]. Previous Malaysian surveys, on the other hand, have found reverse findings, with the bulk of respondents (81.9%) being physically involved.…”
Section: Discussionmentioning
confidence: 90%
“…Characteristically, there is a great heterogeneity among the programs and methods. 7 , 8 Before reviewing the results in the following section, these interventions are elaborated. The following categorization of interventions was chosen because it contributes to a systematic and comprehensive display ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%